2012
DOI: 10.1177/1471301211434677
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to self-management for people with dementia in the early stages

Abstract: People with dementia in the early stages currently experience a care gap, which self-management may address. We explore perceived barriers to self-management. Using a systematic approach (logic mapping), 19 participants (people with dementia, carers, health care professionals and charity representatives) described self-management barriers facing people living with dementia. Thematic content analysis revealed six main themes: the lived experience of dementia, diagnosis, role of carer/family, impact of health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 36 publications
(39 reference statements)
0
70
0
2
Order By: Relevance
“…The most prominent barriers seem to be a deficit focus, lack of services with a positive and enabling approach, and the view of people with dementia as passive recipients of care. Martin et al (2013a), found that skepticism towards the benefits of self-management was evident among carers and health care professionals, but not among people with dementia. In addition, perceived barriers to self-management among people with dementia included worries, fears and lack of confidence, which may be a reflection of the overall negative view of self-management for people with dementia.…”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 99%
“…The most prominent barriers seem to be a deficit focus, lack of services with a positive and enabling approach, and the view of people with dementia as passive recipients of care. Martin et al (2013a), found that skepticism towards the benefits of self-management was evident among carers and health care professionals, but not among people with dementia. In addition, perceived barriers to self-management among people with dementia included worries, fears and lack of confidence, which may be a reflection of the overall negative view of self-management for people with dementia.…”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 99%
“…However, studies highlight the need to ensure that the voice of the person living with dementia is heard and that their needs are balanced with those of the carer. 115 Qualitative studies on SM support for people living with dementia found that information provision may be aimed at carers, leaving people living with dementia feeling powerless, 115 that carers may inadvertently take control away from people living with dementia 109 and that people living with dementia can find support inappropriate or stifling. 132 As one stakeholder put it:…”
Section: Resultsmentioning
confidence: 99%
“…We found 10 studies 37,59,62,106,109,110,115,121,132,136 looking at SM interventions for people living with dementia or cognitive impairment, only one of which included people with dementia and diabetes. 59 This controlled study evaluated the impact of personalised education sessions on people with diabetes and cognitive impairment.…”
Section: Stigma and Barriers To Care For People Living With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…These were two Clinical Psychologists (one female), two Community Psychiatric Nurses (both female), two GPs (one female), and two Psychiatrists working in Older Adults services. [This process is described in full in (Martin et al 2012)]. The reasons were integrated into a summary logic map, eliminating duplicated reasons, or those out with the remit of self-management (e.g., reasons relating to lack of government funding).…”
Section: Introductionmentioning
confidence: 99%